Analisis Peran Humas DPR RI dalam Pengelolaan Instagram @ppid.dprri - Budi, Mauly Helau; Paramita, Sinta (Koneksi, 2025)
In carrying out its duties and performance, the DPR RI institution often reaps pros and cons in society, news about the DPR also often creates a bad image of this institution. Therefore, Public Relations of the DPR RI needs to disseminate information related to the results of DPR RI products. Public Relations currently needs to follow developments in the digital era so that Public Relations of the DPR RI uses the social media Instagram as a digital medium for conveying information. This research uses descriptive qualitative methods as a type of research. Data collection techniques are obtained from the process of observation, interviews and documentation. This research uses the theory of the role of public relations management Fantini, E., Sofyan, M., & Suryana, A. (2021). Researchers also use primary sources through other literature that is relevant to the discussion and reliable which is then processed into data for writing this journal. From the research results, it is known that there are several important factors, one of which is managing information content related to DPR institutions into interesting content. Public Relations of the People's Representative Council of the Republic of Indonesia (DPR RI) continues to innovate in following things that are currently popular or trending in society. Efforts that have been made include conducting research or looking for interesting content references to become a reference in managing information content so that the PPID Instagram account gets more interaction (engagement). However, this is still not optimal. So there needs to be collaboration and innovation in content creation. For this reason, this research is an interesting study with aspects of the role of public relations based on the research conducted. Dalam melaksanakan tugas dan kinerjanya lembaga DPR RI seringkali menuai pro dan kontra dimasyarakat, pemberitaan tentang DPR juga seringkali membuat citra lembaga ini buruk. Maka dari itu Humas DPR RI perlu menyebarluaskan informasi terkait hasil produk DPR RI, Humas saat ini perlu mengikuti perkembangan jaman digital sehingga Humas DPR RI menggunakan media sosial instagram sebagai media digital dalam menyampaikan informasi. Pada penelitian ini menggunakan metode kualitatif deskriptif sebagai jenis penelitian.Teknik pengumpulan data diperoleh dari proses observasi, wawancara, dan dokumentasi. Penelitian ini menggunakan teori peranan manajemen humas Fantini, E., Sofyan, M., & Suryana, A. (2021). Peneliti  juga menggunakan sumber primer melalui literatur lainnya yang relevan dengan pembahasan dan terpercaya yang kemudian diolah menjadi data untuk penulisan jurnal ini. Dari hasil penelitian diketahui bahwa terdapat beberapa faktor penting, salah satunya dalam mengelola konten informasi terkait lembaga DPR menjadi konten yang menarik. Humas Dewan Perwakilan Rakyat Republik Indonesia (DPR RI) terus berinovasi dalam mengikuti hal-hal yang sedang ramai atau sedang tren di masyarakat. Upaya yang telah dilakukan yaitu melakukan research atau mencari referensi konten yang menarik untuk menjadi acuan dalam pengelolaan konten informasi sehingga akun instagram PPID lebih banyak interaksi (engagement). Namun hal ini dirasa masih belum maksimal. Maka perlu adanya kolaborasi dan inovasi-inovasi dalam pembuatan konten. Untuk itulah penelitian ini menjadi kajian yang menarik dengan aspek peranan humas berdasarkan penelitian yang dilakukan.